Mortality after kidney transplantation: 10-year outcomes - DEMİRBAŞ, BAHA TOLGA (My University, 2022)
Objectives: In the past decade, advances in immunological therapy have increased the survival of kidney recipients and their grafts. However, it has not achieved the desired level of improvement. This study aims to reveal the mortality among kidney recipients. Methods: Medical data of the patients, who had undergone kidney transplantation (KT) between November 2010 and December 2020, were retrospectively reviewed. Inclusion criteria were adult kidney recipients, who had died. Exclusion criteria were pediatric recipients, recipients of en bloc and dual KT, recipients with missing data, and recipients with a primary non-functioning graft. The recipients were grouped according to their donor type; Group 1 (from a living donor) and Group 2 (from a deceased donor). Subgroup analyses were done for mortality by time-period post-transplant and for infectious causes of mortality. Results: Of 314 recipients, 35 (11.14%) died. Twenty-nine recipients were included in the study (Group 1: 17 and Group 2: 12). The most common cause of mortality was infection (58.6%), and the second was cardiovascular disease (CVD) (24.1%). Sepsis developed in 29.4% of infection-related deaths, while COVID-19 constituted 23.5% of infection-related deaths. Conclusion: Early diagnosis and treatment of infectious and CVD are important to improve survival in kidney recipients.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Surgery; Cardiovascular; COVID-19; Infection; Kidney transplantation; Mortality; DEATH; DONOR; RISK; RECIPIENTS; GRAFT; Cardiovascular. COVID-19. Infection. Kidney transplantation. Mortality